A Myriad of Exceptions? Challenging the Sonata‐Form Typology for the Classical Repertoire. (28th February 2022) - NEUWIRTH, MARKUS
ABSTRACT: Present‐day sonata theory scholarship increasingly draws on a typology of sonata forms that consists of five interrelated types, placing particular emphasis on the double return and thematic rotation. The present article aims at scrutinising a variety of formal phenomena in the Classical repertoire that potentially challenge, in one way or another, the established sonata‐form typology and its analytic application. This includes the early double return, strong off‐tonic cadences within the recapitulatory action space, false recapitulations as well as false‐false recapitulations, recapitulations launched with P‐based S and off‐tonic recapitulations. The article concludes with a reflection on the epistemological status of the sonata typology and discusses the notion of a modularly conceived Formenlehre .